2012
DOI: 10.1021/jz300792n
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Li Adsorption and Diffusion on MoS2 Zigzag Nanoribbons by Edge Effects: A Computational Study

Abstract: By means of density functional theory computations, we systematically investigated the adsorption and diffusion of Li on the 2-D MoS2 nanosheets and 1-D zigzag MoS2 nanoribbons (ZMoS2NRs), in comparison with MoS2 bulk. Although the Li mobility can be significantly facilitated in MoS2 nanosheets, their decreased Li binding energies make them less attractive for cathode applications. Because of the presence of unique edge states, ZMoS2NRs have a remarkably enhanced binding interaction with Li without sacrificing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
269
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(305 citation statements)
references
References 76 publications
28
269
1
Order By: Relevance
“…By mechanical [4,5] and chemical [6][7][8] exfoliation materials with one or few atomic layers, such as BN, MoS 2 , and WSe 2 , can be obtained from weakly bonded layered compounds. The electronic properties range from zero gap semimetallic graphene over semiconductors with considerable band gaps (e.g., MoS 2 ) to the wideband gap insulator BN.…”
Section: Introductionmentioning
confidence: 99%
“…By mechanical [4,5] and chemical [6][7][8] exfoliation materials with one or few atomic layers, such as BN, MoS 2 , and WSe 2 , can be obtained from weakly bonded layered compounds. The electronic properties range from zero gap semimetallic graphene over semiconductors with considerable band gaps (e.g., MoS 2 ) to the wideband gap insulator BN.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of atoms on the MoS 2 monolayer has been studied in literature [39,52]. by the reversible capacity and operating voltage, which are determined by the chemistry of the electrode material, i.e., its effective redox couples and maximum lithium concentrations [55].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the anode materials should have a large exothermic reaction energy for the transporting ions in order to achieve a large storage capacity [37]. The diffusion barriers for the Li and Na in a monolayer of MoS 2 calculated using density function theory (DFT) are 0.24 [38] and 0.68 eV [34] , respectively, and the Li mobility can be enhanced using the MoS 2 nanoribbons by reducing the dimensions [39]. Defects including single-and few-atom vacancies, antisite, and grain boundary are inevitable, thus the effects of defects on the electronic properties of the MoS 2 have been investigated [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al investigated the adsorption and diffusion of Li atoms on ZMoS 2 NRs for possible applications in Li-ion batteries. 51 It was reported that going from MoS 2 nanosheets to ZMoS 2 NRs, the binding energy and the mobility of Li atoms increase which makes the ZMoS 2 NR a promising cathode materials for Li-ion batteries with high power densities and fast charge/discharge rates.…”
Section: Theoretical Studies On Mosmentioning
confidence: 99%